Proximate Composition and Antioxidant Properties of Orange Mud Crab, Scylla Olivacea - Wan Roslina, Wan Yusof; Fasihuddin, Badruddin Ahmad; Noorasmin, Mokhtar Ahmad; Awang Ahmad Sallehin, Awang Husaini; Swamy, Mummedy (Taylor & Francis, 2019)
The proximate composition and antioxidant properties in the muscle tissues of Scylla olivacea are reported herein. The percentage of carbohydrate was in the range of 1.52% to 3.07 %, while the percentage of protein varied from 13.30% to 17.28%. Meanwhile, the percentage of fat for S. olivacea was found to be ranging from 0.20% to 0.57%. The moisture content in S. olivacea was 60.00%. Generally, no significant differences were observed in both male and female tissues of S. olivacea regarding its total phenolic content, DPPH scavenging and superoxide dismutase activities. However, significant differences were observed for the total flavonoid content and activity of catalase. The present results revealed the nutritional information, enzymatic and non-enzymatic antioxidants status in the tissues of S. olivacea.